DYNAMIC IMAGING OF COGNITIVE IMPAIRMENT IN NICOTINE-DEPRIVED SUBJECTS USING SIMULTANEOUS EEG/FMRI - Long, C; Cole, D; Durcan, M; Matthews, P; Beaver, J; IEEE (2009)
Imaging experiments involving combined Electroencephalography (EEG) and functional MRI (fMRI) acquisitions are becoming increasingly popular primarily because of their ability to offer complementary information about the underlying mechanisms of brain function. In this communication we describe a methodology that combines time-locked EEG and fMRI timeseries with the objective of providing improved characterization of cognitive impairment in nicotine-deprived subjects over conventional independently acquired fMRI. © 2009 IEEE.